The two extremes of physiological tooth resorption in primary tooth with or without the permanent successor tooth - Alberto CONSOLARO; Moacyr Tadeu RODRIGUES; Renata Bianco CONSOLARO; Giovana Gonçalves MARTINS (Dental Press Editora, 2021)
ABSTRACT Introduction: Assessment of two radiographic images reveals two distinct, extreme situations of physiological tooth resorption, characteristic of primary teeth with or without permanent successor, due to partial anodontia. Discussion: In all primary teeth, rhizolysis begins after the completion of formation, thanks to the apoptosis of their cells. When apoptosis induced by cementoblasts has denuded the root of these cells, the process of rhizolysis inevitably begins: This will be accelerated by mediators arising from the pericoronal follicle. When there is no permanent successor due to partial anodontia, rhizolysis occurs extremely slowly, and months later, without the epithelial rests of Malassez that were dead due to apoptosis, alveolodental ankylosis becomes established, and the tooth will gradually be replaced by bone, still within a physiological context. Conclusion: Rhizolysis and physiological tooth resorption may occur rapidly or slowly, early or late, and this depends on the presence of the permanent tooth, or its absence due to partial anodontia.